The Resilience of Indigenous Peoples in North Kalimantan to Corporate Investment - Satyawan, Ignatius Agung; Al-Asyifa, Mutiara Firsty Linggar Nagisa; Putri, Addin Kurnia; Setyanto, Adolfo Eko (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
Indigenous peoples take advantage of land/forest to fulfill their needs. However, in North Kalimantan, the forest functions are increasingly shifting because corporations intend to manage forest areas that reach 69% of the province’s total area, among others, for oil palm plantations. The development of oil palm plantations in North Kalimantan is supported by investments, especially from foreign countries, such as Singapore and Malaysia. Investment funds will influence the progress of oil palm plantations. Although some indigenous peoples have received legal regulations to recognize and protect rights, they still face some impacts, including climate change, environmental pollution, land grabbing, and criminalization. In this case, community resilience is one of the essential capabilities that indigenous peoples must possess, including in North Kalimantan. Indigenous peoples also need various capabilities to anticipate, reduce the impact, and overcome the consequences of corporate development in oil palm plantations. Thus, this article aims to analyze the resilience of indigenous peoples in North Kalimantan in facing investment pressures in oil palm plantations through document review in relevant sources and in-depth interviews with several stakeholders related to indigenous peoples in North Kalimantan. In addition, some previous research has not focused on the resilience of indigenous peoples in North Kalimantan in anticipating or dealing with investment developments that are detrimental to them. The results showed that indigenous people in North Kalimantan had performed resilience by mapping customary lands/territories, monitoring, reporting, and land certificates following legal regulations. Some indigenous people had also referred to the customary law through customary courts, imposing customary sanctions on their members and companies that did not comply with customary norms. Moreover, traditional leaders and institutions have shown an essential role in protecting forests and being the pioneers of agroecology-based economic development